Hadith #31 - Sahih al-Bukhari - al-Ahnaf bin Qays Ø§ÙØ£ØÙÙ Ø¨Ù ÙÙØ³ Ø¨Ù ÙØ¹Ø§ÙÙØ© (Sahih al-Bukhari)
While I was going to help this man (âAli Ibn Abi Talib), Abu Bakra met me and asked, âWhere are you going?â I replied, âI am going to help that person.â He said, âGo back for I have heard Allahâs Messenger (ï·º) saying, âWhen two Muslims fight (meet) each other with their swords, both the murderer as well as the murdered will go to the Hell-fire.â I said, âO Allahâs Messenger (ï·º)! It is all right for the murderer but what about the murdered one?â Allahâs Messenger (ï·
Grade: Sahih

Hadith #1360 - Sahih al-Bukhari - al-Ahnaf bin Qays Ø§ÙØ£ØÙÙ Ø¨Ù ÙÙØ³ Ø¨Ù ÙØ¹Ø§ÙÙØ© (Sahih al-Bukhari)
While I was sitting with some people from Quraish, a man with very rough hair, clothes, and appearance came and stood in front of us, greeted us and said, âInform those who hoard wealth, that a stone will be heated in the Hell-fire and will be put on the nipples of their breasts till it comes out from the bones of their shoulders and then put on the bones of their shoulders till it comes through the nipples of their breasts the stone will be moving and hitting.â After saying that, the person
Grade: Sahih

Hadith #6620 - Sahih al-Bukhari - al-Ahnaf bin Qays Ø§ÙØ£ØÙÙ Ø¨Ù ÙÙØ³ Ø¨Ù ÙØ¹Ø§ÙÙØ© (Sahih al-Bukhari)
I went to help that man (i.e., `Ali), and on the way I met Abu Bakra who asked me, âWhere are you going?â I replied, âI am going to help that man.â He said, âGo back, for I heard Allahâs Messenger (ï·º) saying, âIf two Muslims meet each other with their swords then (both) the killer and the killed one are in the (Hell) Fire.â I said, âO Allahâs Messenger (ï·º)! It is alright for the killer, but what about the killed one?â He said, âThe killed one was eager to kill his opp
Grade: Sahih